White Box Testing Pada Sistem Manajemen Pengelolaan Surat di Sekretariat Rektorat Berbasis Web - Asep Nurdin; Fauziah Fauziah; Ratih Titi Komala Sari (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2021)
Letter is a written communication medium that is made or received by a party related to the implementation of a main task and function of the organization to another party. The Office of the Secretariat of the Rectorate of the National University, which is the working unit for managing correspondence for the leadership, is currently still using manual mail management, both in recording, archiving and disposition. Therefore, the authors designed a mail management system at the secretariat of the web-based rectorate with the PHP programming language and MYSQL database that are easily accessible online via internet browsing, with the aim of making it easier for employees to manage letters, so that work efficiency has increased, disposition becomes faster. and accurate, and the mail management system is becoming more integrated and computerized. The white box testing method is used in system testing, where the results obtained are of the same value for the number of Cyclomatic Complexity City (CC) = 22, Region (R) = 22 and Independent Path = 22, meaning that the logic flow of this system shows that the mail management system is based on This website is correct and appropriate, and free from logical errors.